Pengaruh Dana Pihak Ketiga Dan Non Performing Financing Terhadap Return On Assets (Roa) Pada Bank Umum Syariah Di Indonesia - Inka Triya Septiyani Dewi; Wirman Wirman (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is intended to determine, analyze and describe the effect of Third Party Funds and Non-Performing Financing on Return On Assets at Islamic Commercial Banks in Indonesia for the 2017-2021 period. The data used in this research is descriptive quantitative. This study uses secondary data taken from annual financial report data at Islamic Commercial Banks in Indonesia which are at the OJK and the official website of each bank for the 2017-2021 period. In the data analysis process, the software used is SPSS 21 which consists of descriptive statistical analysis. , classical assumption test (normality test, multicollinearity, autocorrelation and heteroscedasticity), multiple linear regression test, and hypothesis testing (determination test, partial t test and simultaneous F test). The results of this study partially, DPK has no effect on ROA. And NPF has a positive influence on ROA. While the results of the simultaneous test can be concluded that the results of this study are good fit, which means that DPK and NPF simultaneously have a positive and significant effect on ROA.